Relationship of IPO public share allocation with adjusted return and trading volume. - Cheng, Mei Ling. (2008)
The purpose of this study is to examine whether share allocation of newly issued initial public offerings (IPOs) among public, private placement, and reserve categories is related to IPO returns and the daily volume traded. No relationship is found.